2003
DOI: 10.1177/0013161x03257141
|View full text |Cite
|
Sign up to set email alerts
|

Superintendent and School Board Member Turnover: Political Versus Apolitical Turnover as a Critical Variable in the Application of the Dissatisfaction Theory

Abstract: This article explores potential links between school board member and superintendent turnover. Qualitative and quantitative data from 176 school districts in a Northwest state supported the use of the Dissatisfaction Theory as a useful tool in describing the political sequence of events in local school governance and established the necessity of distinguishing between political versus apolitical school board member turnover in studies of this type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 11 publications
2
37
0
1
Order By: Relevance
“…While some governance theories suggest a weak or absent link between the public and their local school governance, Alsbury (2003) found that, on average, 30% of Washington State school board members turned over in every election, with 25% of that turnover caused by defeat or politically motivated resignation and retirement. Over the eight-year study, representing three school board elections, school board member turnover occurred in 97% of the school districts, with 70% of the districts experiencing three or more school board changes representing a change in the voting majority.…”
Section: School Governance Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…While some governance theories suggest a weak or absent link between the public and their local school governance, Alsbury (2003) found that, on average, 30% of Washington State school board members turned over in every election, with 25% of that turnover caused by defeat or politically motivated resignation and retirement. Over the eight-year study, representing three school board elections, school board member turnover occurred in 97% of the school districts, with 70% of the districts experiencing three or more school board changes representing a change in the voting majority.…”
Section: School Governance Theoriesmentioning
confidence: 99%
“…An extensive literature review indicates that nearly every organizational governance study evaluating the dissatisfaction theory, from 1966 to the present, has justified the use of all school board member retirement and resignation as equivalent to incumbent school board member defeat. However, Alsbury (2003) noted the importance of distinguishing the reasons for school board turnover in studies of the dissatisfaction theory. Alsbury (2003) argued that school board turnover not resulting from community discord is outside the theoretical frameworks of the dissatisfaction theory and normally would not lead to the changes in superintendent turnover as predicted by the theory.…”
Section: Defining School Board Turnovermentioning
confidence: 99%
“…Alsbury (2003) examined board members and superintendent turnover links using data from 176 school districts. He listed evidence that supported the use of dissatisfaction theory, a governance tool, and highlighted the importance between political versus apolitical distinctions.…”
Section: Purpose and Research Goalmentioning
confidence: 99%
“…Pasar por alto este aspecto relacional puede limitar nuestra comprensión de una gobernanza exitosa en el distrito escolar y lo que se necesita para acabar esta reforma. Un estudio previo identifica las barreras a la comunicación entre los diferentes niveles de jerarquía en el distrito (Cox & Malone, 2001), que potencialmente conduce a insatisfacción laboral y a una alta rotación (Alsbury, 2003). Por lo tanto, tener en cuenta los vínculos relacionales entre individuos de diferentes niveles dentro de una organización puede ayudar a dirigir la transformación potencial de administradores educativos y a su vez fortalecer el desarrollo sostenido y la gobernanza de un distrito (Daly, Finnigan y Liou, 2014).…”
Section: Aproximación De Red a La Gobernanzaunclassified